2022
DOI: 10.1161/hypertensionaha.122.19378
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Blockers Are Associated With a Lower Risk of Progression From Mild Cognitive Impairment to Dementia

Abstract: Background: Previous studies found that antihypertensive medications (AHMs) acting on the renin-angiotensin system had the potential to reduce the progression from mild cognitive impairment to dementia. However, it remains unclear whether this association differs between ACE (angiotensin-converting enzyme) inhibitors and angiotensin receptor blockers. methods: We conducted a retrospective cohort study in the Alzheimer’s Disease Neuroimaging Initiative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…[90][91][92] A 2022 study found that ARBs are associated with a lower risk of progression to dementia in hypertensive patients with mild cognitive impairment as a baseline. 93 Similar results are found for the neurodegenerative Parkinson's disease. A recently concluded 10-year observational study of patients with ischemic heart disease found that using ARBs that can penetrate the blood-brain barrier significantly reduced the risk of Parkinson's, suggesting a protective effect.…”
Section: Ras In the Brainsupporting
confidence: 67%
“…[90][91][92] A 2022 study found that ARBs are associated with a lower risk of progression to dementia in hypertensive patients with mild cognitive impairment as a baseline. 93 Similar results are found for the neurodegenerative Parkinson's disease. A recently concluded 10-year observational study of patients with ischemic heart disease found that using ARBs that can penetrate the blood-brain barrier significantly reduced the risk of Parkinson's, suggesting a protective effect.…”
Section: Ras In the Brainsupporting
confidence: 67%
“…In line with our hypothesis of a link between heart and brain dysfunction, recent clinical investigations, as well as studies in animal models, have highlighted the beneficial effects promoted by different cardioprotective drugs (i.e., Beta-blockers, Angiotensin Converting Enzyme (ACE) inhibitors, sartans, and Aldosterone receptor antagonists) in Alzheimer’s disease and cognitive dementia. The cardioprotective drugs, in addition to providing preventive effects ( Carey and Fossati, 2022 ), also appear to prevent the neuronal accumulation of Aβ aggregates and result in a significant improvement in memory impairment in some clinical studies as well as in multiple animal models ( Chen et al, 2020 ; Lee et al, 2020 ; Drews et al, 2021 ; Ouk et al, 2021 ; Wang et al, 2021 ; Beaman et al, 2022 ; Deng et al, 2022 ; Mehdipour et al, 2022 ). This evidence points to the possibility that combination therapies containing these compounds may have efficacy for the treatment and prevention of both cardiac diseases and dementia in older adults.…”
Section: Cardiac Sympathetic Innervation and Risk Of Ventricular Arrh...mentioning
confidence: 99%
“…Angiotensin Receptor Blockers and Dementia Prevention: Do Not RAS to a Conclusion Yet Sevil Yasar , Whitney Wharton I n this issue of Hypertension, Deng et al 1 investigate the longitudinal effect of antihypertensive medications acting via the renin-angiotensin system. They examine the effects of both angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin 1 receptor blockers (AT1RB) in participants with hypertension and mild cognitive impairment on all-cause dementia risk and cognitive function.…”
Section: Editorialmentioning
confidence: 99%
“…The study by Deng et al 1 fills part of this knowledge gap. It is the first study evaluating the impact of ATR1B medications on progression from mild cognitive impairment to dementia in people with hypertension accounting for Alzheimer’s disease biomarkers.…”
mentioning
confidence: 99%